Cooperation and mutual aid as a values in the history of Russian Language and Culture - Яроцкая, Галина Сергеевна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The main purpose of the paper presented above is to reveal the characteristics and specific features of linguistic representation of competition / cooperation as value priorities in the relations of subjects of labor activity ("working practice") in the history of Russian Language. Our analysis of the semantic evolution of the Russian lexicon relating to concept of cooperation-mutual aid has uncovered certain value-laden connotations – reoccurring in the meanings of a number of Russian words and phraseological units. Positive connotations are typically associated with lexemes containing a semantic component of cooperation-mutual aid. Elements of working practice such as cooperation and mutual aid are considered to have the attributes of nominative density, meaning that they are brought up and developed by human linguistic consciousness. The conclusion drawn is oriented towards cooperation-mutual aid as a means of achieving harmony in interpersonal relations.